An Overview of Collision Avoidance Approaches and Network Architecture of Unmanned Aerial Vehicles (UAVs) - H. Sawalmeh, Ahmad; Shamsiah Othman, Noor (International Journal of Engineering and Technology, 2018)
As an autonomous vehicle, Unmanned Aerial Vehicles (UAVs) are subjected to several challenges. One of the challenges is for UAV to be able to avoid collision.Â  Many collision avoidance methods have been proposed to address this issue. Furthermore, in a multi-UAV system, it is also important to address communication issue among UAVs for cooperation and collaboration. This issue can be addressed by setting up an ad-hoc network among UAVs. There is also a need to consider the challenges in the deployment of UAVs, as well as, in the development of collision avoidance methods and the establishment of communication for cooperation and collaboration in a multi-UAV system. In this paper, we present general challenges in the deployment of UAV and comparison of UAV communication services based on its operating frequency. We also present major collision avoidance approaches, and specifically discuss collision avoidance approaches that are suitable for indoor applications. We also present the Flying Ad-hoc Networks (FANET) network architecture, communication and routing protocols for each Open System Interconnection (OSI) communication layers.Â